Innovate integration of guided inquiry learning (GIL) and project-based learning (PjBL) to enhance students’ science literacy - Nova Florentina Ambarwati Ambarwati; Retno Dwi Suyanti; Aaron Loh; Ribka Kariani Br Sembiring; Darinda Sofia Tanjung; Dyan Wulan Sari HS (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop and implement an integrated learning model combining Project-Based Learning (PjBL) and Guided Inquiry Learning (GIL) to enhance science literacy in students within the advanced science education course. The study was conducted to students from the Elementary School Teacher Education Program at the Catholic University of Santo Thomas, focusing on the topic of States of Matter. A quasi-experimental design with a pre-test – post-test control group design was employed, where the control group received conventional teaching methods, and the experimental group engaged in the integrated PjBL-GIL model. The results reveal a significant difference in science literacy improvement between the groups. The experimental group, using the integrated PjBL-GIL model, showed a greater improvement (22.4%) compared to the control group (7.7%). Statistical analysis using a two-sample t-test confirmed the significance of this difference, with a t-value of 5.16 and a p-value of 0.000, indicating a statistically significant improvement in the experimental group. The effect size, measured by Cohen's d, was 2.53, indicating a large effect. ANCOVA results showed that even after controlling for baseline differences, the experimental group still demonstrated significantly higher post-test scores (p-value = 0.000). Furthermore, Pearson’s correlation analysis revealed a significant positive relationship between collaboration and science literacy improvement (r = 0.62, p = 0.01), emphasising the importance of collaboration in enhancing learning outcomes. These findings suggest that the integrated PjBL-GIL model is effective in improving critical thinking, problem-solving skills, and the application of scientific concepts. And it is recommended that this model be expanded in science education in Indonesia to further improve the quality of learning and students' science literacy.